Kesantunan Berbahasa Indonesia Guru dan Siswa Madrasah Diniyah Al-Akbar Bungbungan Bluto Sumenep (dalam Perspektif Pragmatik) - Arifah, Siti (STID Raudlatul Iman Sumenep, 2019)
Imperative imperative politeness is speech politeness in the form of an order from the speaker to the spoken partner to do something in accordance with the instructions of the speaker. In pragmatics, there are seventeen forms of pragmatic imperative modesty from the seventeen forms in this study. Only in this study are six forms of pragmatic imperative politeness, namely the form of politeness of imperative pragmatics which implies requests, orders, invitations, requests for permission, prohibitions, and congratulations. The speech is a speech between the teacher and students which is analyzed from the Indonesian imperative politeness Kesantunan tuturan imperatif merupakan kesantunan tuturan yang berupa perintah dari penutur kepada mitra tutur untuk melakukan sesuatu sesuai dengan perintah penutur.Dalam ilmu pragmatik terdapat tujuh belas wujud kesantunan pragmatik imperatif dari ketujuh belas wujud tersebut dalam penelitian ini hanya ditemukan enam wujud kesantunan pragmatik imperatif yaitu wujud kesantunan pragmatik imperatif yang mengandung makna permintaan, suruhan, ajakan, permintaan izin, larangan, dan pemberian ucapan selamat. Tuturan tersebut merupakan tuturan antara guru dan siswa yang dianalisis dari kesantunan tuturan imperatif bahasa Indonesia